Forest fires in Indonesia: impacts and solutions - Applegate, G.; Smith, R.; Fox, J.J.; Mitchell, A.; Packham, D.; Tapper, N.; Baines, G. (Resources for the Future, Center for International Forestry Research (CIFOR) and Institute of Southeast Asian Studies (ISEAS), 2002)
The severe fires that burned over 9.7 million ha of Indonesia in 1997/98 occurred in an El Niño year. Much of the impact of fires could have been avoided if appropriate fire management systems were in place and policies relating to fire and land use were appropriate to deal with the situation. The fires affected a large portion of the Indonesian population causing economic hardship and disruption to commerce and short and long term health problems. The smoke and haze generated by the fires also caused disruptions and economic loss to many neighbouring countries, causing diplomatic tensions. Much of the haze was generated by burning peat which not only generates 17 times more smoke than forests, but as a fossil fuel contributed over 700 tonnes of carbon dioxide in harmful emissions over an eight-month period. This chapter provides an assessment of the fire situation in 1997/98 and some technical and institutional policy recommendations to reduce the risk of fire prior to and during the next El Niño event currently predicted to occur in 2001.